# 1차원 가우시안 적분

둘러보기로 가기 검색하러 가기

##### 간단한 소개

\begin{align} x_1 = &-\frac{b}{3 a}\\ &-\frac{1}{3 a} \sqrt[3]{\frac{2 b^3-9 a b c+27 a^2 d+\sqrt{\left(2 b^3-9 a b c+27 a^2 d\right)^2-4 \left(b^2-3 a c\right)^3}}{2}}\\ &-\frac{1}{3 a} \sqrt[3]{\frac{2 b^3-9 a b c+27 a^2 d-\sqrt{\left(2 b^3-9 a b c+27 a^2 d\right)^2-4 \left(b^2-3 a c\right)^3}}{2}}\\ x_2 = &-\frac{b}{3 a}\\ &+\frac{1+i \sqrt{3}}{6 a} \sqrt[3]{\frac{2 b^3-9 a b c+27 a^2 d+\sqrt{\left(2 b^3-9 a b c+27 a^2 d\right)^2-4 \left(b^2-3 a c\right)^3}}{2}}\\ &+\frac{1-i \sqrt{3}}{6 a} \sqrt[3]{\frac{2 b^3-9 a b c+27 a^2 d-\sqrt{\left(2 b^3-9 a b c+27 a^2 d\right)^2-4 \left(b^2-3 a c\right)^3}}{2}}\\ x_3 = &-\frac{b}{3 a}\\ &+\frac{1-i \sqrt{3}}{6 a} \sqrt[3]{\frac{2 b^3-9 a b c+27 a^2 d+\sqrt{\left(2 b^3-9 a b c+27 a^2 d\right)^2-4 \left(b^2-3 a c\right)^3}}{2}}\\ &+\frac{1+i \sqrt{3}}{6 a} \sqrt[3]{\frac{2 b^3-9 a b c+27 a^2 d-\sqrt{\left(2 b^3-9 a b c+27 a^2 d\right)^2-4 \left(b^2-3 a c\right)^3}}{2}} \end{align}

$$ax^3+bx^2+cx+d=0$$

[/pages/4488973/attachments/2379915 53ca622976ecf6c23e06c56de8077ed0.png]

##### 관련기사
• 네이버 뉴스 검색 (키워드 수정)

##### 블로그

1. $$\int\int_{\mathbb{R}^2}e^{-x^2-y^2}dA$$

$$\int\int_{\mathbb{R}^2}e^{-x^2-y^2}dA= \int_{0}^{2\pi}\int_{0}^{\infty}e^{-r^2}rdrd\theta=2\pi\int_{0}^{\infty}re^{-r^2}dr=2\pi[-\frac{1}{2}e^{r^2}]_{0}^{\infty}=\pi$$

2. $$\int_{-\infty}^{\infty}e^{-\frac{x^2}{2}}dx$$

$$\int\int_{\mathbb{R}^2}e^{-x^2-y^2}dA= \int_{-\infty}^{\infty}\int_{-\infty}^{\infty}e^{-x^2-y^2}dxdy=(\int_{-\infty}^{\infty}e^{-x^2}dx)(\int_{-\infty}^{\infty} e^{-y^2}dy)=(\int_{-\infty}^{\infty}e^{-x^2}dx)^2$$

$$\int_{-\infty}^{\infty}e^{-x^2}dx =\sqrt{\pi}$$

$$x=\frac{t}{\sqrt{2}}$$,

$$\int_{-\infty}^{\infty}e^{-\frac{x^2}{2}}dx=\sqrt{2\pi}$$